FIB‐4 stage of liver fibrosis predicts incident heart failure among HIV‐infected and uninfected patients. Issue 4 (30th August 2017) - So‐Armah, Kaku A.; Lim, Joseph K.; Lo Re, Vincent; Tate, Janet P.; Chang, Chung‐Chou H.; Butt, Adeel A.; Gibert, Cynthia L.; Rimland, David; Marconi, Vincent C.; Goetz, Matthew B.; Rodriguez‐Barradas, Maria C.; Budoff, Matthew J.; et al.
Abstract : Liver fibrosis is common, particularly in individuals who are infected with human immunodeficiency virus (HIV). HIV‐infected individuals have excess congestive heart failure (CHF) risk compared with uninfected people. It remains unknown whether liver fibrosis stage influences the CHF risk or if HIV or hepatitis C virus (HCV) infection modifies this association. Our objectives were to assess whether 1) stage of liver fibrosis is independently associated with incident CHF and 2) the association between stage of liver fibrosis and incident CHF is modified by HIV/HCV status. Participants alive on or after April 1, 2003, in the Veterans Aging Cohort Study were included. Those without prevalent cardiovascular disease were followed until their first CHF event, death, last follow‐up date, or December 31, 2011. Liver fibrosis was measured using the fibrosis 4 index (FIB‐4), which is calculated using age, aminotransferases, and platelets. Cox proportional hazards regression models were adjusted for cardiovascular disease risk factors. Among 96, 373 participants over 6.9 years, 3844 incident CHF events occurred. FIB‐4 between 1.45 and 3.25 (moderate fibrosis) and FIB‐4 > 3.25 (advanced fibrosis/cirrhosis) were associated with CHF (hazard ratio [95% confidence interval], 1.17 [1.07‐1.27] and 1.65 [1.43‐1.92], respectively). The association of advanced fibrosis/cirrhosis and incident CHF persisted regardless of HIV/HCV status. Conclusion : Moderate and advanced liver fibrosis/cirrhosis are associated with an increased risk of CHF. The association for advanced fibrosis/cirrhosis persists even among participants without hepatitis C and/or HIV infection. Assessing liver health may be important for reducing the risk of future CHF events, particularly among HIV and hepatitis C infected people among whom cardiovascular disease risk is elevated and liver disease is common. (Hepatology 2017;66:1286‐1295)